CHANGING FACE OF MULTIPLE SCLEROSIS IN THE UNITED KINGDOM 1990–2010. AN INCIDENCE AND PREVALENCE STUDY. Issue 11 (9th October 2013) - Mackenzie, Isla S; Morant, Steven V; Bloomfield, Glenys A; MacDonald, Thomas M; O'Riordan, Jonathan I
Abstract : Background: Our knowledge of the impact of Multiple Sclerosis throughout the UK as a whole is often based on extrapolation from small regional studies. There have been few nationwide studies. Methods: We sought to rectify this using the General Practice Research Database (GPRD) to estimate the incidence and prevalence of MS by age, and describe secular trends and geographic variations within the UK over the 20 year period between 1990 and 2010. Results: The numbers of patients with up–to–standard follow up time on the GPRD increased from 1.1 million in 1990 to at least 4.0 million between 2006 and 2010. The GPRD population included about 8% of the UK population in 2010, and their age and sex distribution were similar to those of the whole population. During the study period the prevalence of MS increased by about 2.4% per year (95% CI 2.3%, 2.6%) reaching 2, 858 per million (pm) in women (95% CI 2, 787, 2, 931) and 1, 131 pm in men (95% CI 1, 086, 1, 177) by 2010. There was a consistent downward trend in incidence of MS reaching 97.2 pm/yr (95% CI 80.3, 117.5) in women and 48.0 pm/yr (95% CI 39.3, 58.7) in men by 2010. Peak incidence occurred between ages 40–50 years and maximum prevalence between ages 55–60 years. Women accounted for 72% of prevalent and 71% of incident cases. Scotland had the highest proportion of cases of MS with an incidence almost double that of Wales. We looked at the variation in incidence and prevalence rates for MS between UK regions. We found a statistically significant trend in both incidence and prevalence of MS with latitude, but in both cases the significance of the trend was lost when Scotland was excluded from the analysis. There was significant variation in both the incidence and prevalence of MS between different UK regions (p<0.001) in addition to any possible trend with latitude. Discussion: Our study provides a comprehensive picture of the prevalence and incidence of MS throughout the UK. We estimate that 126, 669 people were living with MS in the UK in 2010 (2, 034 pm population), and that 6, 003 new cases were diagnosed that year (96.4 pm/yr). There is an increasing population living longer with MS, which has important implications for resource allocation for MS in the UK. Funding: This study was funded by a grant from the Multiple Sclerosis National Therapy Centres.